Semi-Analytical Analysis of Fractional Model in Thin-Film Flow Incorporating Oldroyd 6-Constant Fluids - Younas, H. M.; Iqbal, Shaukat; Ali, Javaid; Ahsan, Muhammad; El-kenawy, El-Sayed M. (Journal of Environmental Accounting and Management, 2026)
The special combination of viscous and elastic behaviors of Oldroyd fluids makes them an invaluable subject for study in many scientific and engineering applications. While the Oldroyd-B (3-Constant) model is extensively employed for unidirectional steady flows, it is unsuitable for situations involving extensional flows and convergent flow channels. This paper suggests an Oldroyd fluid fractional analysis in thin-film flow, using the Oldroyd 6-Constant model for lifting and drainage scenarios. Highly nonlinear fractional differential equations are solved using fractional calculus and the Optimal Homotopy Asymptotic Method (OHAM). Residual calculations verify the validity and convergence of the solutions.